PEMANFAATAN LEARNING MANAGEMENT SYSTEM (LMS) SEBAGAI MEDIA PEMBELAJARAN DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS TADULAKO - Ahmad Setiaji; Dwi Rohma Wulandari; Hadisuddin (KINESIK, 2022)
This study aims to determine the use of the Learning Management System (LMS) as a medium of learning communication between students and lecturers at the Faculty of Social and Political Sciences, Tadulako University. This research is based on a qualitative descriptive method approach which aims to be used to provide an overview and describe the entire object under study in accordance with the data obtained. Data collection techniques were carried out by means of in-depth interview observations and documentation. The informants in this study were four (6) people. The data analysis technique used is based on the guidelines for the steps of qualitative research data analysis, namely data reduction, data presentation and drawing conclusions.Based on the results of research LMS as a medium of learning communication between students and lecturers at the Faculty of Social and Political Sciences, Tadulako University. The site offers various features so that it can support learning within the Faculty of Social and Political Sciences, Tadulako University. The site is very easy to access anywhere and can even be accessed using a handphone. In addition to the advantages in terms of ease of accessing this web, it can be accessed anywhere, another advantage obtained by students is the advantage from an economic point of view, where the student feels that learning through this site saves more on quota usage compared to learning using other online applications.